2015
DOI: 10.1002/cjas.1338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pension fund freezing on firm performance and risk

Abstract: This study considers the effect of freezing defined benefit pension funds on shareholder risk and returns. The conditional models used in this study directly assess the effects of a pension fund freeze on returns and on systematic and residual risk. While pension fund freezes do not significantly affect performance or systematic risk, they do significantly reduce short-term residual risk. Pension fund freezes therefore do not generally present significant financial advantages to shareholders. Only shareholders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The literature has established that the static nature of the CAPM or the extended FF model may be impregnated with specification errors [3,4,5,6]. Recent applications of conditional models, for instance, include pension fund performance and the analysis of the impact of the informational content of extra-financial performance scores on systematic risk (e.g., [48,49]). However, none of these studies provide specification error tests or discuss possible endogeneity issues.…”
Section: Five-factor Augmented Fama-french Conditional Modelmentioning
confidence: 99%
“…The literature has established that the static nature of the CAPM or the extended FF model may be impregnated with specification errors [3,4,5,6]. Recent applications of conditional models, for instance, include pension fund performance and the analysis of the impact of the informational content of extra-financial performance scores on systematic risk (e.g., [48,49]). However, none of these studies provide specification error tests or discuss possible endogeneity issues.…”
Section: Five-factor Augmented Fama-french Conditional Modelmentioning
confidence: 99%
“…Other evidences to analyse the relationship between risk assessment and financial performance are cited by Ahmad Abdel Rahim& et al [1] who used multi regression analysis to investigate the impact of liquidity risk and solvency on financial performance measured by (return on asset and earning per share); the findings indicated that the financial assessment is a statistically associated with size, liquidity and solvency of Jordanian manufacturing firms on Amman Stock Exchange. Recently, Claudia Champagne & et al [6] used conditional probability model to evaluate the impact of pension fund freeze on return and risk. It was found that there is an insignificant relationship between pension fund freeze on systematic risk, but significantly reduced short-term residual risk.…”
Section: Other Sectorsmentioning
confidence: 99%
“…• The partial eta squared of the covariate variables in terms of x 1 , x 2 ,lnx 3 and the interactions between x 1 x 2 and lnx 2 account for (0.057-0.212-0.210-0.013) of the variation in the total dependent variables, i.e., from the medium effect to large effect, finally to small effect. From table (6), the researcher revealed that:…”
Section: Glm Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…surge in plan freezes to stop future benefit accruals as an attempt to reduce risk in the pension scheme (Munnell & Soto, 2007). Further research on pension freezes followed: agency conflicts and directors in relation to DB pension freezes (Vafeas & Vlittis, 2018); executive compensation manipulation before freezes (Stefanescu et al, 2018); actuarial assumption manipulation before freezes (Comprix & Muller, 2011); and concerning firm value and performance (Champagne et al, 2017;Yu, 2016). Even after a freeze, the plan sponsor must continue to bear the pension risk for the vested and retired participants over decades, which has led to a stream of literature covering internal pension risk management concerning corporate financing policy for investment opportunities.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%